Ethics, technology and future challenges: A bioethical perspective of the digital society - Villalobos-Antúnez, José Vicente; Guerrero-Lobo, José Francisco; Prats-Palma, Belisario; Rojas-Torrejón, Francisco (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The future challenges of the digital society are analyzed. From phenomenological-hermeneutical perspective, the idea of an ethics of technology considers the digital society as technical device. The pertinent literature allows, first, to study disruptive technology as generator of social changes, which, in turn, transform the forms of the facticity of life. In this way, the ethics of the material society serves as argument to analyze the ethics in the digital society. Taking philosophical bioethics as instrument, it is concluded that the digital society sets challenges for life, which must be faced for survival.